2018
DOI: 10.1080/19420862.2018.1466767
|View full text |Cite
|
Sign up to set email alerts
|

The “less-is-more” in therapeutic antibodies: Afucosylated anti-cancer antibodies with enhanced antibody-dependent cellular cytotoxicity

Abstract: Therapeutic monoclonal antibodies are the fastest growing class of biological therapeutics for the treatment of various cancers and inflammatory disorders. In cancer immunotherapy, some IgG1 antibodies rely on the Fc-mediated immune effector function, antibody-dependent cellular cytotoxicity (ADCC), as the major mode of action to deplete tumor cells. It is well-known that this effector function is modulated by the N-linked glycosylation in the Fc region of the antibody. In particular, absence of core fucose on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
211
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(229 citation statements)
references
References 148 publications
5
211
0
Order By: Relevance
“…However, core-fucosylation is likely most known for its capacity to adjust the humoral immune response by altering antibody-dependent cellular cytotoxicity (ADCC). Thus, different strategies for reducing core-fucosylation in therapeutic monoclonal antibodies have been developed to enhance ADCC 8 . Notably, FUT8 is upregulated in numerous types of cancer, suggesting that blocking its activity could be a promising strategy for improving antitumor immune responses 9 .…”
mentioning
confidence: 99%
“…However, core-fucosylation is likely most known for its capacity to adjust the humoral immune response by altering antibody-dependent cellular cytotoxicity (ADCC). Thus, different strategies for reducing core-fucosylation in therapeutic monoclonal antibodies have been developed to enhance ADCC 8 . Notably, FUT8 is upregulated in numerous types of cancer, suggesting that blocking its activity could be a promising strategy for improving antitumor immune responses 9 .…”
mentioning
confidence: 99%
“…Another important Fc-mediated immune effector function that plays the most important role in depleting tumor cells is called antibody-dependent cellular cytotoxicity (ADCC). It has been proved previously that the absence of core fucose on Fc N-glycan structures can lead to enhanced ADCC activity (23, 24). It has also been confirmed that apart from afucosylation, galactosylation levels could also influence ADCC activity; however, the role of afucosylation is more prominent.…”
Section: Resultsmentioning
confidence: 99%
“…The mutation abrogating the N-glycosylation at Asn in the Fc region aborts the interaction with FcγRIIIa [50]. The fucosylated antibody was reported to reduce the binding a nity to FcγRIIIa [51]. In Humira ® , the fucosylated N-glycan is contained with the ratio of 10 % [52], and thus relatively low a nity to FcγRIIIa was detected when high concentrations of Humira ® (15 µg/ml) and TNFα (40 ng/ml) were used (Fig.…”
Section: Discussionmentioning
confidence: 97%